Reactive powder concrete incorporating metakaolin and fly ash for monumental architectural objects. Issue 1 (August 2020) - Dvorkin, L; Zhitkovsky, V; Lushnikova, N; Fursovych, M
Abstract: The paper gives coverage on the properties of reactive powder concrete, incorporating metakaolin and fly ash and polyacrylate superplasticizer. There are given results of comparative research of reactive powder concrete (RPC) containing silica fume. There are also considered the impact of curing conditions on the strength of RPC specimens. The combination of fly ash and metakaolin is the effective composite mineral additive that allows to obtain RPC without silica fume. The optimal dosage of metakaolin in composite admixture from the point of maximum flexural and compressive strength was about 10% by cement weight. The curing of the RPC specimens in the hot water at t=80°C increases compressive strength of concrete at 20-25%. Adding the combination of metakaolin and fly ash with permits to achieve RPC high values of mechanical properties compatible to RPC containing silica fume. High fluidity of fresh concrete along with high performance of hardened concrete allows to apply RPC for manufacturing architectural elements of non-linear geometry, thin structures, and other.